OP0153 The art of tapering glucocorticoids (GC): A systematic review of studies reporting tapering strategies and outcomes in patients with rheumatoid arthritis (RA). (23rd January 2014) - Volkmann, E.R.; Rezai, S.; Furst, D.E.; Woodworth, T.
Abstract : Background: Strategies to taper GC in RA vary considerably and the effects of different tapering strategies on clinical outcome measures are unknown. Objectives: To identify GC tapering studies and to evaluate their comparative efficacy and safety with respect to clinical outcomes. Methods: We conducted a systematic literature search in PubMed and Cochrane Central to identify publications from January 1972 to February 2011. Search terms comprised 3 blocks: disease (RA), intervention (GC and related terms) and outcome (withdrawal/tapering). To maximize our yield, tapering was defined as decreasing to 7.5 or 0 mg daily. The review was divided into 3 stages: titles, abstracts, and full articles. Each was assessed by 2 team members and rejected if it fulfilled one of the following exclusion criteria: (1) Not pertaining to adults with RA, (2) Not a case-control study, cohort study, clinical trial, database/registry, (3) Not pertaining to GC withdrawal, (4) Extension study. Discordant assessments were resolved by a third party arbiter (DEF). Results: From an initial listing of 1265 articles, 6 articles met review criteria; each described a different tapering strategy (Table). All were randomized controlled trials. Only 1 study described an objective disease activity measure (DAS44) used to guide the GC taper. 2 Only 4 studies reported whether patients successfully tapered/withdrew GC. Among the 251 patients who initiated a taper, 54 (22%) failed to taper/withdraw. Studies with the lowest failure rates included patients with early RA (<1yr), while studies with the highest failure rates included patients with longer disease durations (>1yr). One study compared baseline disease characteristics of patients who successfully versus unsuccessfully tapered and showed that successful tapering was associated with younger age and premenopausal status. 3 No studies compared clinical outcome measures or adverse events in patients who successfully versus unsuccessfully tapered. Conclusions: There is marked variability in reported GC tapering regimens and many patients fail to withdraw from GC. Well-designed studies, considering age and disease duration, are needed to determine effective and safe strategies for tapering GC. References: Lancet 1997;350:309-18. Arthritis Rheum 2005;52:3381-90. Scand J Rheumatol 2007;36:351-8. Ann Rheum Dis 2008;67:656–63. Ann Rheum Dis 2009;68:1715-1720. Brit J of Rheumatol 1998;37:930-936. Disclosure of Interest: None Declared